Descripción de las características ultrasonográficas de los órganos abdominales de dos especies del género Saimiri (mono fraile) mantenidos en cautiverio en Lima, Perú - Ventolini San Martin, Maria Grazia (2020)
In this thesis I worked with two species Saimiri boliviensis and Saimiri macrodon, both in the genus Saimiri. They are found in the tropical forests of South America, in the low jungle and part of the high jungle up to 1,900 meters above sea level. The IUCN classified Saimiri boliviensis and Saimiri macrodon as "Least concern" with the population of these two species in decline. In this thesis, I used the images and video files obtained from the abdominal ultrasound performed with the Esaote ultrasonographic equipment and the linear transducer during the annual health check. The images of 11 squirrel monkeys’ specimens (8 males and 3 females) between 2 and 17 years old, in the Parque de las Leyendas zoo, were evaluated. From this evaluation, the ultrasonographic characteristics of the liver, spleen, stomach, kidneys, intestinal loops, testicles, gallbladder, bladder and uterus were described. With the information collected, the topography, margins, echogenicity, ecotexture and architecture of them were described. This species presents similarities with three species with which it was compared, Cebus albifrons, Cebus apella and Sapajus macrocephalus. Being ultrasound a non-invasive, fast and easy method to evaluate abdominal organs and from this description of the abdominal organs; This technique will help preventive medicine and improve diagnostics in wild species in different places.